Carinata, the Sustainable Crop for a Bio-based Economy: Production Recommendations for the Southeastern United States - Sheeja George; Ian M. Small; Pratap Devkota; Henry Y. Sintim; Mike J. Mulvaney; Ramon Leon; Silvana Paula-Moraes; Isaac Esquivel; Rick Bennett; Alison Poknywinski; Dan Geller; James J. Marois; et al. (EDIS)
Brassica carinata is a non-food industrial oilseed crop that can be grown in the winter in the southeast US without impacting food, feed, or fiber crops. Carinata is a low carbon advanced renewable fuel feedstock and a good source of animal protein. Carinata research in the SE US through a public-private partnership has developed a comprehensive body of knowledge regarding carinata agronomics, life cycle analysis, best management practices and economics. This article aims to help growers and others interested in carinata to understand its biology, agronomy, and production aspects.